Clinical profile and inheritance pattern of CYP21A2 gene mutations in patients with classical congenital adrenal hyperplasia from 10 families - Sarita Yadav (Indian Journal of Endocrinology and Metabolism, 2015)
Context: Congenital adrenal hyperplasia (CAH) is an autosomal recessive metabolic disorder caused by mutations in the CYP21A2 gene. Genetic diagnosis of 21-OH deficiency causing CAH is more complicated than any other monogenic disorder due to high variability of the locus. The disease has a wide spectrum of clinical variants making it difficult to establish a genotype-phenotype correlation. Therefore, family studies are necessary to ascertain parental genotype and segregation of the mutant allele among the offspring. Aim: The present study aimed to identify CYP21A2 gene mutations and analyze the segregation pattern in CAH trios (patients and their parents). Materials and Methods: A total of ten families having at least one CAH child were recruited. Results: Out of 31 children from ten families, 15 were affected with CAH and 13 of /them (12 females and 1 male) were available for genetic testing. One family had all the children affected with CAH. Compound heterozygous mutations were identified in seven patients (53.8%) whereas p.P30L, In2 and δ8 bp mutations were present in homozygous state in three (23.1%), two (15.3 %) and one (7.6%) patient respectively. Conclusions: In majority of the families, mutant alleles observed in the patients were inherited from the parents whereas three families showed sporadic mutations without any paternal or maternal origin. This indicated their novel occurrence due to misalignment of the parental genes and /or large deletion of the gene. Female preponderance was noted in the CAH families and also among the patients raising the possibility of survival advantage among females.